Prevalence of dysmenorrhea and associated factors and its effect on daily academic activities among female undergraduate students of Hawassa University College of Medicine and Health Sciences, Hawassa, Ethiopia - Belayneh, Wondu; Kassaye, Zerai; Arusi, Temesgen; Abera, Netsanet; Hantalo, Admassu; Melkamu, Biruk; Gutulo, Muluken (Frontiers in Reproductive Health, 2023)
Abstract Background: Dysmenorrhea is pain during menstrual flow and is the most common gynecologic complaint in the reproductive age group. The severity of dysmenorrhea ranges from mild to severe pain, which affects their academic activities during menstruation. Objective: To assess the prevalence, associated risk factors, and effects of dysmenorrhea on academic activities among Hawassa University students from April 1–30, 2021. Methods: A cross-sectional study was employed, and a systematic random sampling technique was used to get 348 study participants. Standardized, self-administered questionnaires were used to obtain relevant data. The severity of pain was assessed using the verbal multidimensional scoring system and the Numerical Pain Rating Scale (NPRS) methods. The collected data was entered into Epinfo version 7 and exported to SPSS version 21 for analysis, and then descriptive statistics and logistic regression analysis were performed. Results: The prevalence of dysmenorrhea was 80% (277). Of these, by using the verbal multidimensional scoring system, 47.6% (132) had mild pain, 39.7% (110) had moderate pain, and 12.6% (35) had severe pain. Whereas, using the Numeric Pain Rating Scale (NPRS), 21.7% (60) experienced mild, 33.2% (92) moderate, 37.5% (104) severe, and 7.6% (21) very severe pain. It had a negative effect on academic activities such as loss of class concentration (p = 0.00), affected study time (p = 0.00), sleep disturbances (p = 0.00), affected personal relationships (p = 0.00), and absenteeism (p = 0.00). Associated factor included being sexually active, family history of dysmenorrhea, and presence of depression. Conclusion: Dysmenorrhea is prevalent in this study and has a significant impact on academic activities. Family history of dysmenorrhea, being sexually active, and presence of depression are associated factors Keywords: dysmenorrhea, academic activities, family history, Hawassa University